Challenges and Opportunities in Scaling up Architectural Applications of Mycelium-Based Materials with Digital Fabrication - Selina Bitting; Tiziano Derme; Juney Lee; Tom Van Mele; Benjamin Dillenburger; Philippe Block (Biomimetics, 2022)
In an increasing effort to address the environmental challenges caused by the currently linear economic paradigm of “produce, use, and discard”, the construction industry has been shifting towards a more circular model. A circular economy requires closing of the loops, where the end-of-life of a building is considered more carefully, and waste is used as a resource. In comparison to traditional building materials such as timber, steel and concrete, mycelium-based materials are renewable alternatives that use organic agricultural and industrial waste as a key ingredient for production, and do not rely on mass extraction or exploitation of valuable finite or non-finite resources. Mycelium-based materials have shown their potential as a more circular and economically competitive alternative to conventional synthetic materials in numerous industries ranging from packaging, electronic prototyping, furniture, fashion to architecture. However, application of mycelium-based materials in the construction industry has been limited to small-scale prototypes and architectural installations due to low mechanical properties, lack of standardisation in production methods and material characterisation. This paper aims to review the current state of the art in research and applications of mycelium-based materials across disciplines, with a particular focus on digital methods of fabrication, production, and design. The information gathered from this review will be synthesised to identify key challenges in scaling up applications of mycelium-based materials as load-bearing structural elements in architecture and suggest opportunities and directions for future research.